Hydrogen Peroxide Electrochemical Sensor Based on Ag/Cu Bimetallic Nanoparticles Modified on Polypyrrole - Yanxun Guan; Fen Xu; Lixian Sun; Yumei Luo; Riguang Cheng; Yongjin Zou; Lumin Liao; Zhong Cao (Sensors, 2023)
Due to the strong oxidizing properties of H2O2, excessive discharge of H2O2 will cause great harm to the environment. Moreover, H2O2 is also an energetic material used as fuel, with specific attention given to its safety. Therefore, it is of great importance to explore and prepare good sensitive materials for the detection of H2O2 with a low detection limit and high selectivity. In this work, a kind of hydrogen peroxide electrochemical sensor has been fabricated. That is, polypyrrole (PPy) has been electropolymerized on the glass carbon electrode (GCE), and then Ag and Cu nanoparticles are modified together on the surface of polypyrrole by electrodeposition. SEM analysis shows that Cu and Ag nanoparticles are uniformly deposited on the surface of PPy. Electrochemical characterization results display that the sensor has a good response to H2O2 with two linear intervals. The first linear range is 0.1–1 mM (R2 = 0.9978, S = 265.06 μA/ (mM × cm2)), and the detection limit is 0.027 μM (S/N = 3). The second linear range is 1–35 mM (R2 = 0.9969, 445.78 μA/ (mM × cm2)), corresponding to 0.063 μM of detection limit (S/N = 3). The sensor reveals good reproducibility (σ = 2.104), repeatability (σ = 2.027), anti-interference, and stability. The recoveries of the electrode are 99.84–103.00% (for 0.1–1 mM of linear range) and 98.65–104.80% (for 1–35 mM linear range). Furthermore, the costs of the hydrogen peroxide electrochemical sensor proposed in this work are reduced largely by using non-precious metals without degradation of the sensing performance of H2O2. This study provides a facile way to develop nanocomposite electrochemical sensors.